(3CSGSjGJ GdLZQGajI GdHTQjI (B/s - (3GdSYOj, YHGS aGVds ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2002)
(3GdLZQGajI GdHTQjI heOGQSgG,GdEfSGf,GdEfSGf hGdHjFI GdWHjYjI,GdGbJUGO GdHTQj,GdGSJjWGf GdHTQjs
(3eUGOQ HGddZI GdYQHjI U(B.453(3; eUGOQ HGdZI GdEfcdjRjI U(B.467 (3jhLO faS GdcJGH HQbe C(B/1788s
Keywords: (3GdLZQGajG GdHTQjIs